POLITIK HUKUM PEMEKARAN DAERAH DALAM NEGARA KESATUAN REPUBLIK INDONESIA - Iskatrinah Iskatrinah (DE LEGA LATA: JURNAL ILMU HUKUM, 2017)
Indonesia is a country which territory is divided into areas of the province, which is divided over the district and the city. Formation of the provinces, counties, and cities are set by law, may be merging some areas or parts of areas that side by side or division of a region into two regions or more, which is basically intended to improve public services in order to accelerate the realization of public welfare, in addition to as a means of political education at the local level. Forming regions should consider of various factors such as economic capacity, potential of the region, area, population, and consideration of the social aspects of political, social, cultural, defense and security as well as consideration and other terms that allow the region can organize and realize the purpose of establishing the area and the granting of regional autonomy.